Kernel and Properties In Up Translate and Down Translate Intuitionistic Ring Fuzzy: Kernel dan Sifatnya pada Translasi Naik dan Turun Ring Fuzzy Intuitionistik - Pratama, Dian (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
Intuitionistic fuzzy ring is a generalized of ring combined with intuitionistic fuzzy sets. It also has impact on ideal so it become intuitionistic fuzzy ideal. The existence of the generalization process, needs to be studied about the properties of kernel at ring homomorphism in which we know that the kernel of a ring homomorphism is ideal. In addition, the study of fuzzy sets there are operators that are subject to membership and non membership functions. One of the known operators is up translates. This research examines the structure of the kernel at homomorphism rings in fuzzy intuitionistic rings. After that the structure of the kernel is also examined if the intuitionistic fuzzy ring is subjected to an up translates operator.